Molecular epidemiology and antimicrobial resistance features of Acinetobacter baumannii clinical isolates from Pakistan - Karah, Nabil (Ann Clin Microbiol Antimicrob, 2020)
BACKGROUND: Acinetobacter baumannii is a Gram-negative opportunistic pathogen with a notorious reputation of being resistant to antimicrobial agents. The capability of A. baumannii to persist and disseminate between healthcare settings has raised a major concern worldwide. METHODS: Our study investigated the antibiotic resistance features and molecular epidemiology of 52 clinical isolates of A. baumannii collected in Pakistan between 2013 and 2015. Antimicrobial susceptibility patterns were determined by the agar disc diffusion method. Comparative sequence analyses of the ampC and bla(OXA-51-like) alleles were used to assign the isolates into clusters. The whole genomes of 25 representative isolates were sequenced using the MiSeq Desktop Sequencer. Free online applications were used to determine the phylogeny of genomic sequences, retrieve the multilocus sequence types (ST), and detect acquired antimicrobial resistance genes. RESULTS: Overall, the isolates were grouped into 7 clusters and 3 sporadic isolates. The largest cluster, Ab-Pak-cluster-1 (bla(OXA-66) and ISAba1-ampC-19) included 24 isolates, belonged to ST2 and International clone (IC) II, and was distributed between two geographical far-off cities, Lahore and Peshawar. Ab-Pak-clusters-2 (bla(OXA-66), ISAba1-ampC-2), and -3 (bla(OXA-66), ISAba1-ampC-20) and the individual isolate Ab-Pak-Lah-01 (ISAba1-bla(OXA-66), ISAba1-ampC-2) were also assigned to ST2 and IC II. On the other hand, Ab-Pak-clusters-4 (bla(OXA-69), ampC-1), -5 (bla(OXA-69), ISAba1-ampC-78), and -6A (bla(OXA-371), ISAba1-ampC-3) belonged to ST1, while Ab-Pak-cluster-6B (bla(OXA-371), ISAba1-ampC-8) belonged to ST1106, with both ST1 and ST1106 being members of IC I. Five isolates belonged to Ab-Pak-cluster-7 (bla(OXA-65), ampC-43). This cluster corresponded to ST158, showed a well-delineated position on the genomic phylogenetic tree, and was equipped with several antimicrobial resistance genes including bla(OXA-23) and bla(GES-11). CONCLUSIONS: Our study detected the occurrence of 7 clusters of A. baumannii in Pakistan. Altogether, 6/7 of the clusters and 45/52 (86.5%) of the isolates belonged to IC I (n = 9) or II (n = 36), making Pakistan no exception to the global domination of these two clones. The onset of ST158 in Pakistan marked a geographical dispersal of this clone beyond the Middle East and brought up the need for a detailed characterization.